Pochonia chlamydosporia Induces Plant-Dependent Systemic Resistance to Meloidogyne incognita - Ghahremani, Zahra; Escudero, Nuria; Saus, Ester; Gabaldón, Toni; Sorribas, F. Javier (Frontiers in Plant Science, 2019)
Meloidogyne spp. are the most damaging plant parasitic nematodes for horticultural crops worldwide. Pochonia chlamydosporia is a fungal egg parasite of root-knot and cyst nematodes able to colonize the roots of several plant species and shown to induce plant defense mechanisms in fungal-plant interaction studies, and local resistance in fungal-nematode-plant interactions. This work demonstrates the differential ability of two out of five P. chlamydosporia isolates, M10.43.21 and M10.55.6, to induce systemic resistance against M. incognita in tomato but not in cucumber in split-root experiments. The M10.43.21 isolate reduced infection (32–43%), reproduction (44–59%), and female fecundity (14.7–27.6%), while the isolate M10.55.6 only reduced consistently nematode reproduction (35–47.5%) in the two experiments carried out. The isolate M10.43.21 induced the expression of the salicylic acid pathway (PR-1 gene) in tomato roots 7 days after being inoculated with the fungal isolate and just after nematode inoculation, and at 7 and 42 days after nematode inoculation too. The jasmonate signaling pathway (Lox D gene) was also upregulated at 7 days after nematode inoculation. Thus, some isolates of P. chlamydosporia can induce systemic resistance against root-knot nematodes but this is plant species dependent.